Manajemen Pelayanan Keterbukaan Informasi Publik Pada Dinas Komunikasi dan Informatika, Sandi dan Statistik Kota Cilegon - Hujjatul Maryam Maryam; Agus Sjafari; Riswanda Riswanda (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2022)
Public Information Disclosure is important in realizing Good Governance and realizing human rights in obtaining Public Information in a transparent and easy manner. Cilegon City is one of the big cities in Banten Province. In carrying out the service of Public Information Disclosure at the Cilegon City Government, the role of the Main Public Information Management Officer is in the Office of Communication and Information, Passwords and Statistics of the City of Cilegon. In carrying out its role in providing public information disclosure services. Has several problems: Lack of human resources, Lack of supporting facilities and infrastructure, Lack of satisfaction level of information requesters, Lack of HR capabilities, No place for public complaints, Lack of responsiveness of service providers to information requesters, Lack of coordination between PPID, Lack of discipline of service providers, Value of information disclosure public distended in 2019. This study uses a qualitative descriptive. The results of this study indicate that the public information disclosure service at Diskominfo Cilegon City is quite good